Investigation of prompt γ ray emission for online monitoring in ion therapy. (March 2015) - Steinschaden, D; Brunner, S E; Dichtl, H; Fuchs, H; Georg, D; Hirtl, A; Marton, J; Pichler, A
Abstract: The aim of this study was to investigate the principle of using prompt γ ray emissions for the determination of the position of the Bragg peak in radiotherapy with carbon ions. Developing a system for online monitoring in ion therapy with the required accuracy is an important step for the utilization of modern accelerator facilities for medical purposes. The investigations were carried out by Monte Carlo studies in the framework of the simulation environment GATE. In the course of these investigations, production parameters of prompt γ rays, like the emission rate and energy distribution were determined as a function of the primary carbon ion energy and the penetration depth in a water target. A possible connection between these parameters and the position of the Bragg peak and the dose delivery was investigated. Within the energy spectrum an energy range was identified in which the production rate of the γ rays shows a significant drop right after the Bragg peak.